The effect of performance appraisal system on staff productivity and job motivation - A case study on EPF staff Malacca / Eryani Mohd Jasuri - Mohd Jasuri, Eryani (Faculty of Business Management, 2001)
This study is aimed to evaluate the staff feelings about the performance appraisal system and how it's effect on staff productivity and job motivation. The study covers the present staff of EPF Malacca and about 50% respondents are selected. Two hypotheses forwarded and consist of the higher is the degree of agreement of staff with appraisal system, the higher the staff motivation and the higher is the degree of agreement of staff with appraisal system, the higher the productivity. The results from the test association for staff feelings toward the performance appraisal, and other variables of productivity and motivation indicate that: amongst all the elements of productivity, only volunteer to do an extra work, low absenteeism and low turnover are significantly correlated with feelings of satisfaction toward the performance appraisal system. While for motivation, factors of opportunity career growth, good working condition, interesting work, symphatetic help with personal problems, are significantly correlated with feelings of satisfaction toward the performance appraisal system. This result is further confirmed by regression model. Only average motivation significantly correlated with the dependent variable, which is an average feeling.